Putting Oneself in the Body of Others: A Pilot Study on the Efficacy of an Embodied Virtual Reality System to Generate Self-Compassion - Cebolla, Ausiàs; Herrero, Rocío; Ventura, Sara; Miragall, Marta; Bellosta-Batalla, Miguel; Llorens, Roberto; Baños, Rosa Ma (Frontiers in Psychology, 2019)
Compassion-based interventions (CBIs) have been shown to be effective for increasing empathy and compassion, and reducing stress, anxiety, and depression. CBIs are based on constructive meditations where imagery abilities are essential. One of the major difficulties that participants report during the training is the difficulty related to imagery abilities. Virtual Reality (VR) can be a useful tool to overcome this limitation because it can facilitate the construction and sustainment of mental images. The machine to be another (TMTBA) uses multi-sensory stimulation to induce a body swap illusion. This system allows participants to see themselves from a third perspective and have the illusion of touching themselves from outside. The main objective of the present study was to analyze the efficacy of a self-compassion meditation procedure based on the TMTBA system versus the usual meditation procedure (TAU) in increasing positive affect states, mindful self-care, and adherence to the practice, and explore the influence of imagery abilities as moderators of the effects of the condition on adherence. A sample of 16 participants were randomly assigned to two conditions: TMTBA-VR and TAU. All participants had to listen to an audio meditation about self-compassion and answer questionnaires before and after the training. The TMTBA-VR condition also had a body swap experience at the end of the meditation while listening to self-compassionate messages. Afterwards, they were invited to practice this meditation for two weeks and then measured again. After the compassion practice, both conditions significantly increased positive qualities toward self/others, decreased negative qualities toward self, and increased awareness and attention to mental events and bodily sensations, with no differences between the conditions. After two weeks, both conditions showed a similar frequency of meditation practice and increases in specific types of self-care behaviors, with the frequency of clinical self-care behaviors being significantly higher in TMTBA. Finally, lower imagery ability in the visual and cutaneous modality were moderators of the efficacy of the TMTBA (vs. TAU) condition in increasing adherence to the practice. Embodied VR could be an interesting tool to facilitate and increase the efficacy of CBIs by facilitating the construction of positive and powerful mental images.